Pengaruh Tomat dan Buah Jeruk Nipis Sebagai Bahan Pemutih Alami Gigi - Shania Salsabila; Member Reni Purba; Steven Wijaya; Rizky Mulyanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Abstract. Introduction; appearance is one of the aspects that a person really cares about in carrying out social interactions in today's modern times. Objectives; know the difference between the effectiveness of tomatoes (Solanum Lycopersicum) and lime (Citrus limon L) as natural teeth whitening agents. Method; This type of experimental laboratory research with pretest and posttest only with control group design. The analytical test used was the one-way ANOVA test and posthoc LSD. showed that there were differences in the value of color observations in the tomato fruit extract, lemon extract, and the chromid peroxide group after soaking for 1 hour, 3 hours, and 5 hours. Conclusion; that there is an effect of tomato (Solanum Lycopersicum) and lime (Citrus limon L) as natural ingredients for teeth whitening